PAI Teacher's Efforts In Instilling Akhlakul Karimah Attitude Of Autistic Students At MI Miftahul Ulum Puntir - Lubadasari, Puja; Khurotin, Siti (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to identify the efforts of Islamic Religious Education (PAI) teachers in shaping akhlakul karimah attitudes in autistic students at MI Miftahul Ulum Puntir. This research uses a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation. The results showed that PAI teachers implemented various strategies, such as individualized approaches, the use of concrete and visual methods, and intensive assistance. Teachers also create a conducive learning environment by providing role models, positive motivation, and encouraging social interaction between students. Although this school is not SLB-based and faces challenges in the learning process, teachers' efforts show positive results in the formation of akhlakul karimah for autistic students. This study concludes that the right approach and a supportive environment can help shape the character of students with special needs and contribute to the development of character education in inclusive madrasah. The findings are expected to contribute to the development of character education for children with special needs in madrasah.